(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This paper looks at the issues and prospects of environmental sustainability in Uttarakhand India, Chamoli District. The Chamoli district is situated at the heart of the Himalayas, in Garhwal division. The district of Chamoli is Uttarakhands second biggest area. The latitudinal range of this area is 30oN-31oN, with the longitudinal scale of 78oE-80oE. The surface capacity of this region is 8030 km2 as per records. Chamoli District is at just a very attractive location for Uttarakhand in the light of its glorious scenery, pilgrims or admiration centers, the diversity, tourist attractions and strategic safety.Chamoli Tourism is the largest source of revenue and income because it is not only the mix of flora and fauna but also its amazingly wealthy biological diversity differentiate the Valley of the National Flower Park. Natural beauty of this district also attracts visitors from across the globe. In specific from the finest Flower Valley nature reserve at the different places of Uttarakhand. The religious and vacation tourism of the region will also attract tourists.Nevertheless, Chamoli is one of the poorest regions of India and is extremely vulnerable to natural disasters like floods, earthquakes, etc. Due to imminent natural hazards, no main infrastructure or building projects have been sufficiently established by the government. Development in the area is thus a significant obstacle to preserve peace with nature. The focus of this study is on sample field surveys through assessments, conversations with local communities and visitors as well as secondary data sources such as newsletters, publications, magazines etc.